Cervical leukocytes and spontaneous preterm birth. (February 2016) - Hunter, Patricia J.; Sheikh, Sairah; David, Anna L.; Peebles, Donald M.; Klein, Nigel
Highlights: Hypothesis that defects in cervical immunity might be a feature of spontaneous preterm birth (SPTB). A prospective observational study of 120 pregnancies at risk of SPTB because of the mother's history. Cervical leukocytes, cytokines and chemokines were sampled at 12–25 weeks using a cytobrush. Early SPTB (<34 weeks) lacked cervical macrophages and had low CCL2 (<75 ng/g total protein). Abstract: The objective was to characterise cervical leukocyte populations and inflammatory mediators associated with term and recurrent spontaneous preterm birth (SPTB) in pregnant women with a history of SPTB. A prospective observational study was undertaken on 120 women with a history of SPTB. A cytobrush was used to sample cells from the cervix at 12–25 weeks' gestation. Cells were enumerated and characterised by flow cytometry. Cytokines and chemokines were also measured. Participants were then grouped according to delivery at term (>36 + 6 weeks), late SPTB (34–36 + 6 weeks) or early SPTB (<34 weeks). Differences in leukocyte sub-populations, cytokine and chemokine levels were compared with outcome. Cervical leukocytes comprised up to 60% of the host-derived cells. Most of these (90–100%) were polymorphonuclear cells (PMN). Most of the remaining cells were mucosal macrophages expressing CD68 and CD103 in addition to markers shared with blood-borne monocytes. Failure to detect cervical macrophages in at least 250, 000 cervical epithelial cells was a feature of women who experienced early SPTB (6 out of 6 cases, 95% CI 61–100%) compared with 34% (30 out of 88 cases, 95% CI 25–43%, P  < 0.001) of women delivering after 34 weeks. CCL2 (MCP-1) was also low in SPTB before 34 weeks and levels above 75 ng/g and/or the presence of macrophages increased the specificity for birth after 34 weeks from 66% to 82% (55 out of 67 cases, 95% CI 73–91%). Absence of cervical macrophages and low CCL2 may be features of pregnancies at risk of early SPTB.